Pengaruh Insentif, Digitalisasi Dan Relawan Pajak Terhadap Kepatuhan Wajib Pajak Dengan Kualitas Pelayanan Sebagai Variabel Moderasi - Ristiyana, Rida; Atichasari, Anna Sofia; Indriani, Ridha (Owner : Riset dan Jurnal Akuntansi, 2024)
This research aims to determine the effect of Incentives, Digitalization and Tax Volunteers on Taxpayer Compliance with Service Quality as a moderating variable. This type of research is quantitative where researchers use primary data with data collection techniques through questionnaires. The research population is Micro, Small and Medium Enterprises (MSMEs) who live in Tangerang City. The sampling technique used simple random sampling, with a total sample of 393 respondents. The data analysis method uses Partial Least Square (PLS) using SmartPLS 3.0 software. The results of this research simultaneously show that incentives, digitalization and tax volunteers have an effect on taxpayer compliance, then the research results partially show that incentives, tax volunteers and service quality have a positive and significant effect on taxpayer compliance, while digitalization has no effect on taxpayer compliance. Most MSMEs experience difficulties in implementing the digitalization system, even though facilities have been improved, there are still many people who do not utilize these facilities, because errors often occur in the tax digitalization system which makes taxpayers find it difficult to carry out digital-based administration systems and it can be said that access and the use of technology for registration, payment and reporting is still low. The MRA test results show that service quality is unable to moderate the influence of incentives, digitalization and tax volunteers on taxpayer compliance.